Potential growth of productive areas ecologically equipped (APEA) adherens of the FICEI - Sandro Turina; Giuseppe Confessore; Maurizio Turina; Ilaria Barbante (European Regional Science Association (ERSA), 2015)
The working group, in valuing the scientific publications made in previous years on the quantification and measurement of the indicators of 'attraction' of a territory, tried to find a sustainable development model, verifing the effect that the recent introduction APEA (Industrial Areas Ecologically equipped) has as a tool enabler the 'site location', in order to verify the effect that the reduction in the time of issuance of the necessary permits to the settlements has on potential for growth of one or more 'cluster competitor' adhering to FICEI (Italian Federation Industrial Consortia). The Ficei is a federated structure admitted to the program of support for technology transfer RIDITT, funded by the Ministry of Economic Development and the study has allowed us to develop decision support tools able to impact more on the ability to 'strategic positioning' of industrial clusters in regime of mutual competition or in competition. In particular, the simulation of the growth effect of the industrial areas APEA in regime of competition inter and intra cluster was made possible through the development of data base aggregates to which it was decided to associate logistic functions who have displayed in 'real time' the growth potential in the regime of a renewed action of technology transfer provided by the ministerial program. For the realization of the above system has realized an application capable of guiding the choices of strategic positioning simulating the growth potential compared to 'contender cluster' with a method characterized by the introduction of parametric functions of saturation of the population of enterprises and the introduction of parameters 'predation' capable of simulating the competitive effect of one or more clusters Italian the pilot area object of study. The working method used was, therefore, the following: (i) mapping of the distinctive features of the cluster Ficei-Apea; (ii) identification of the effect of technology transfer through saturation parameters to be included in logistics functions; (iii) identification of the parameters of predation required to simulate the effect of competitive industrial clusters; (iv) processing the data in the light of the selected indicators and representation of the dynamics of growth through comparative analysis of the functions of saturation. The results of the research group will permit to operate in application environments more in line with the needs of the area of innovation by helping to assess the sustainability for businesses of new business models in an area characterized by a higher degree of competition. The publication of this work is, therefore, the evolution of the work presented last year confirming the effort made by the research team to make available to the scientific community, predictive models for impact assessment that public support has on local SMEs and the related question of development.
Keywords: G21; G29; O30; O31; O32; O33; 330; Financial institution; Financial Market; Innovations; Transfer of Technology